Morphological and quantitative evaluation of buffalo preantral follicles in different reproductive phases - Oba, Eunice [UNESP]; Carvalho, Fabíola Christian Almeida de [UNESP]; Mota, Adriano Vitti [UNESP]; Camargos, Aline Sousa [UNESP]; Ramos, Alcides de Amorim [UNESP]; Magalhaes, Luis Carlos Oña [UNESP] (My University, 2010)
The objective of this research was to estimate the population of preantral follicles in prepubertal (P), adult (A) and pregnant (PR) female buffaloes, as well as to observe the different degeneration types and rates of preantral follicles. For this study, 18 Murrah-Mediterranean buffalo ovaries (one from each female) were divided into three experimental groups: Group 1 – six P buffalo ovaries; Group 2 – six A buffalo ovaries; Group 3 – six PR buffalo ovaries. The ovaries were processed for classical histology analysis. Preantral follicle population was estimated by the follicle counting that used the oocyte nucleus as a marker and a correction factor. Follicle quality evaluation was based on basal membrane integrity, cell density, presence or absence of pyknotic bodies and oocyte integrity. Follicles were classified according to their morphology (primordial, primary and secondary), and quality (normal, degenerated Type I or Type II). Follicle degeneration was evaluated via ultrastructural analysis using a transmission electron microscope. The preantral follicle population per ovary that comprised morphologically normal, degenerated Type I and degenerated Type II follicles were 23.664, 3.071 and 3.586 in P; 15.081, 5.480 and 8.686 in A; 7.603, 2.496 and 14.374 in PR, respectively. For prepubertal, adult and pregnant buffaloes, higher proportions of morphologically normal follicles were observed in primordial (87.75%), primary (89.96%) and secondary follicles (78.19%), respectively. Primary follicles had higher proportion of Type I degeneration, whereas primordial and secondary follicles had more Type II degeneration in P, A and PR buffaloes, respectively. The preantral follicle proportion of morphologically normal and degenerated Type I significantly differed within the three evaluated reproductive phases.
Keywords: Preantral follicle; Buffalo cows; Histology; Ultrastructural; Prepubertal; Adult; Pregnant